The mechanical properties of oil palm shell (OPS) lightweight aggregate concrete containing palm oil clinker as a partial sand replacement - Christben, Jimmy (2014)
Oil palm shell (OPS) and palm oil clinker (POC) is a waste from palm industries which is excess from a process where electricity was generated in palm oil factories. The use of this POC material as partial sand replacement material in concrete will help lower the pollution to the environment. This thesis presents an experimental study on effect of POC content towards mechanical properties of OPS LWAC Two types of mixes that has been used in this study that is plain OPS LWAC containing 100% natural river sand and another mix containing POC as partial sand replacement. POC used as partial sand replacement from ranges from 0% to 20%. All specimens were cast and subjected to water curing until the testing date. Specimens were tested for compressive strength and flexural strength up to 28 days. The highest compressive strength and flexural strength achieved reaching up to 34.4 MPa and 3.42 MPa respectively at age 28 days with 20% POC as partial sand replacement. Conclusively use of POC up to 20% increases the compressive strength and flexural strength of OPS lightweight aggregate concrete.